A Conceptual and Large-Scale Empirical Examination of the Welcoming Empowerment Monitoring Approach (WEMA) for School Safety and Substance Use Reduction. (July 2021) - Astor, Ron Avi; Benbenishty, Rami; Watson, Kate R.
Purpose: Research shows that many evidence-based school programs are not sustained after the demonstration period is complete. This article outlines the Welcoming Empowerment Monitoring Approach and builds on data at each school—to address school safety and reduce substance use. Method: The study used California Healthy Kids Survey data across 145 schools in Southern California at five points in time over an 8-year period. Results: From project inception through 3 years after the project completed, all manifestations of school victimization dropped and were sustained. Lifetime alcohol and marijuana use also declined for all students during the overall period assessed. Discussion: Schools, districts, and regions tailored interventions according to each school's and region's specific needs. Combinations of ground-up solutions, evidence-based programs, building internal capacity, and connecting the school to resources helped reduce victimization and substance use.